Exploratory analysis of differences in sperm morphology in Nelore and Gir (Bos indicus) bulls - Lucio, Aline Costa de [UNESP]; Ferraudo, Antonio Sergio [UNESP]; Oliveira, Leticia Zoccolaro de [UNESP]; Carmo, Adriana Santana do [UNESP]; Alves, Benner Geraldo; Alves, Kele Amaral; Almeida, Solange; Deragon, Luis Alfredo; Pereira, William [UNESP]; Carneiro, Luisa Cunha [UNESP]; Martins Hossepian de Lima, Vera Fernanda [UNESP] (Springer, 2014)
The aim of this study was to evaluate the effects of breed and season on semen quality parameters of zebu bulls. Data (1,632 registers) of semen production from Gir (n = 4) and Nelore (n = 15) bulls were collected between October 2005 and November 2009. The ejaculates were collected twice a week during various seasons (summer, fall, winter, and spring) and evaluated for the following semen parameters: ejaculate volume, sperm concentration, sperm motility, forward progressive motility (FPM), and sperm morphology. Factor analysis was used to determine the relationship among variables. The effect of breed (Gir and Nelore) and season and their cross effect on each parameter and extracted factor were tested using ANOVA. A negative correlation (P < 0.05) was observed between FPM and proximal droplet, as well as with abnormal loose head, abnormal small head, pouch formation, abnormal mid-peace, and strongly folded tail. Gir bull sperm showed more major defects, detached acrosome, and minor FPM (P < 0.01), whereas Nelore bulls showed a higher number of sperm with normally loose head.
Keywords: Bos indicus; Factor analysis; Gir; Nelore; Sperm morphology